Comparison between Si/SiO2 mid‐gap interface states and deep levels associated with silicon‐oxygen superlattices in p‐type silicon. Issue 10 (13th May 2016) - Simoen, Eddy; Jayachandran, S.; Delabie, A.; Caymax, M.; Heyns, M.
Abstract: In this paper, the deep levels found by deep‐level transient spectroscopy in Si‐O superlattices on p‐type silicon substrates are compared with the band of near mid‐gap hole traps typically observed at the Si/SiO2 interface. In addition, the impact of a post‐deposition Forming Gas Annealing is investigated. A large similarity between the two material systems is reported, which indicates that similar silicon‐oxygen bonds may be responsible for the deep hole traps.(© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)